Clinical Features and Outcomes of Pediatric MYH7-Related Dilated Cardiomyopathy - de Frutos, Fernando; Ochoa, Juan Pablo; Webster, Gregory; Jansen, Mark; Remior, Paloma; Rasmussen, Torsten B; Sabater-Molina, Maria; Barriales-Villa, Roberto; Girolami, Francesca; Cesar, Sergi; Fuentes-Cañamero, M Eugenia; Alvarez García-Rovés, Reyes; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Although genetic variants in MYH7 are the most frequent cause of pediatric genetic dilated cardiomyopathy (DCM), there are no studies available describing this entity. We sought to describe clinical features, analyze variant location, and explore predictors of bad prognosis in pediatric MYH7-related DCM. METHODS AND RESULTS: We evaluated clinical records from 44 patients (24 men; median age at diagnosis, 0.54 [interquartile range, 0.01-10.8] years) with pathogenic/likely pathogenic variants in MYH7 diagnosed with DCM at pediatric age (<18 years) followed at 13 international centers. We also explored risk factors associated with a composite end point of end-stage heart failure defined as heart transplantation or heart failure-related death. Twenty-two patients (50%) were diagnosed at age <6 months, including 7 (16%) at birth. Left ventricular (LV) hypertrabeculation features were present in 15 (38%), particularly among patients with genetic variants in the head domain. After a median follow-up of 6.1 years (interquartile range, 1.9-13.4), 15 patients (36%) required a heart transplant (n=14) or died due to end-stage heart failure (n=1), 15 patients (36%) persisted with systolic dysfunction despite treatment, 12 (29%) had a significant increase in LV ejection fraction, and 2 were lost to follow-up. Overall, end-stage heart failure event rate was 25% at 5 years. New York Heart Association class III to IV (hazard ratio [HR], 7.67 [95% CI, 2.16-27.2]; P=0.002) and LV ejection fraction ≤35% (HR, 4.00 [95% CI, 1.11-14.4]; P=0.03) were the best predictors of bad prognosis. CONCLUSIONS: Pediatric MYH7-related DCM is characterized by early onset, frequent LV hypertrabeculation, and poor prognosis. Advanced New York Heart Association class and low LV ejection fraction emerged as predictors of end-stage heart failure.
Keywords: těžké řetězce myosinu; dítě; Myosin Heavy Chains; fenotyp; novorozenec; srdeční selhání; Adolescent; genetics; dilated cardiomyopathy; genetická predispozice k nemoci; Retrospective Studies; prognóza; dilatační kardiomyopatie; předškolní dítě; Heart Failure; lidé; Cardiac Myosins; Risk Factors; Ventricular Function, Left; pediatric; Cardiomyopathy, Dilated; Prognosis; Genetic Predisposition to Disease; kojenec; Female; Mutation; MYH7; srdeční myosiny; mutace; Male; ženské pohlaví; Humans; funkce levé komory srdeční; mužské pohlaví; Child; Infant, Newborn; rizikové faktory; Infant; Heart Transplantation; transplantace srdce; Child, Preschool; Phenotype; mladiství; retrospektivní studie